"Doing our best for patient safety": An international and interprofessional qualitative study with spinal manipulative therapy providers in community-based settings. (December 2021) - Funabashi, Martha; Holmes, Michelle M.; Pohlman, Katherine A.; Salsbury, Stacie; O'Beirne, Maeve; Vohra, Sunita; Mior, Silvano
Abstract: Background: Patient safety research is expanding from hospitals to community-based healthcare settings. Knowledge gaps persist among manual therapy professions that may impede patient safety initiatives within musculoskeletal care settings. Objectives: To describe perceptions of patient safety among chiropractors and physiotherapists who provide spinal manipulation therapy (SMT). Design: Qualitative descriptive study. Method: Cross-sectional data were collected using the SafetyNET Survey t o Support Q uality Improvement . SMT providers (n = 705) in 3 countries completed surveys, with 84 providing written responses to an open-ended question about patient safety. Qualitative thematic analysis described providers' perceptions about patient safety within their practice. Results: SMT providers' perceptions were influenced by professional, patient, and practice setting factors. Five themes and 10 supporting categories were developed. Doing Our Best for Patient Safety concerned Avoiding Mistakes and Prioritizing Safety. Putting Patients First focused on Developing Relationships and Individualizing Care. Working and Learning Together advocated for Interprofessional Communication and Collaborative Learning . Organizing Practice Processes emphasized Standardizing Procedures and Benchmarking Progress. Considering Practitioner Identity highlighted how Recognizing Difference among SMT providers and Challenging Fears of other healthcare professionals and patients about SMT were important for enhancing patient safety. Conclusion: Findings align with World Health Organization guiding principles that the nature of healthcare settings influence patient safety strategies. Most responses focused on individual strategies to prevent adverse events. However, this approach may overlook the benefits of identifying and documenting adverse events, setting time to discuss adverse events with clinic members, standardizing clinical practices, and building transparent patient safety cultures across healthcare professions and settings. Highlights: Spinal manipulation providers report prioritizing safety. Interprofessional communication and collaborative learning facilitate patient safety. Lack of standardized clinical protocols and benchmarking are patient safety barriers. Findings align with guiding principles of the WHO Global Patient Safety Action Plan .